Analisis Faktor-Faktor Penyebab Terjadinya Pengangguran dan Urbanisasi Pemuda di Desa Tamansari Kecamatan Karangmoncol Kabupaten Purbalingga Provinsi Jawa Tengah - Wijaya, Placenta Abshar; Suprihanto, John; Riyono, Bagus (Jurnal Pendidikan Ekonomi Undiksha, 2020)
Some of the problems that are frequently found in villages are unemployment and urbanization among rural youth. This study aimed to (1) Identify the factors that cause unemployment and urbanization among the youth in Tamansari Village, Karangmoncol Subdistrict, Purbalingga Regency, Central Java Province, (2) Analyze the causes of unemployment and urbanization among the youth in Tamansari Village, Karangmoncol Subdistrict, Purbalingga Regency, Central Java Province. This was a qualitative descriptive study. The informants in this study were the young people in Tamansari Village, and the Head of Tamansari Village. The data were collected through interview, observation, documentation, and online data search techniques. The analysis in this study was carried out using descriptive qualitative analysis and comparative analysis. The results of the study showed that (1) There are some factors that cause unemployment and urbanization among the youth in Tamansari Village, Karangmoncol Subdistrict, Purbalingga Regency, Central Java Province, (2) Several causes of unemployment and urbanization among the youth in Tamansari Village, Karangmoncol Subdistrict, Purbalingga Regency, Central Java Province were revealed.